STAD Method as an Effort to Improve Student Learning Outcomes on Etiquette and Dhikr Material at Mts S Al-Qornis Pamarayan - Murti (Journal of Action Research in Islamic Education, 2025)
This study investigates the effectiveness of the Student Team Achievement Division (STAD) method in enhancing student learning outcomes on the topic of prayer etiquette and dhikr at MTs S Al-Qornis Pamarayan. As a cooperative learning model, STAD emphasizes collaborative learning within heterogeneous student groups. Employing a quantitative approach with a quasi-experimental design, the research involved eighth-grade students divided into an experimental group (taught using the STAD method) and a control group (taught using conventional methods). Data were collected through learning outcome tests, observations, and questionnaires, and analyzed using both descriptive and inferential statistical techniques. The findings revealed that students in the STAD group demonstrated significantly higher learning outcomes, greater participation in group discussions, increased motivation, and improved understanding of the material compared to the control group. Moreover, the STAD approach fostered a more interactive and enjoyable classroom environment, encouraging students to confidently express their ideas and benefit from peer collaboration. These results suggest that STAD not only enhances academic performance but also supports the development of social skills. Therefore, the STAD method presents a viable and effective alternative for educators seeking to promote active, cooperative, and meaningful learning experiences in the classroom.